Financial covenants and their restrictiveness in European LBOs – an assessment in the aftermath of the financial crisis. (1st January 2012) - Achleitner, Ann-Kristin; Bock, Carolin; Tappeiner, Florian
Financial covenants play a crucial role in mitigating agency conflicts in loan agreements of high leverage. In a European-wide qualitative survey among private equity experts, we assessed the impact of the financial crisis on financial covenants in leveraged buyout transactions. We concentrated on the factors that drive covenant restrictiveness by measuring the change of headroom as the most influential factor determining restrictiveness. The survey of 25 lead arrangers and private equity sponsors indicates that financial covenants mainly serve the purpose of managing the risk of the transactions and that leverage, interest cover, cash flow cover, and capex constitute the most important covenants. Their restrictiveness increased heavily during the financial crisis. The liquidity of debt markets, the deal pressure for mandated lead arrangers and the private equity sponsor's history of covenant breaches represent the drivers of highest importance for covenant restrictiveness.